Implementasi Pengaturan Terkait Kewenangan Perangkat Desa Adat Marga terhadap Peristiwa Perkawinan Nyentana - Deli Bunga Saravistha; Ni Putu Sutrisna Dewi; Luh Merry Dyanthi (Journal of Education and Culture, 2023)
The factors that cause the occurrence of "Nyentana" marriage within a family is a situation where there is no male offspring. Looking at the kinship structure in Bali that adheres to the patrilineal system, where the wife enters her husband's family, it can be said that the position of men in Balinese families is very important. In marriages, divorce often occurs, as stated in Article 39 paragraph (2) of Law Number 16 of 2019, which is an amendment to Law No. 1 of 1974 concerning marriage. The purpose of this research is to determine the legal regulation of Balinese customary law as a legal umbrella regarding the position of a divorced man in Nyentana marriage and the importance of legal provisions in the community in the form of "awig-awig" that regulate the rights and obligations of a divorced man in Nyentana marriage that occurs in Marga Village. This research method uses the Normative Juridical research method to find legal rules and principles used as a basis to discuss legal issues related to the legal position of men after divorce in Nyentana marriage as well as the lack of agreement regarding the regulation of the legal position of men after divorce in Nyentana marriage in the form of "awig-awig". This research uses a conceptual approach, statute approach, and historical approach. The conceptual approach is used to discuss the urgency of rules that discuss the legal position of men after divorce in Nyentana marriage. The statute approach is used to examine legal rules related to Nyentana marriage. The historical approach is used to understand the customary legal review used as a legal basis in Nyentana marriage. The legal material search technique in this paper uses a literature study technique, which is then analyzed using qualitative analysis.